Condensation-curable thermally conductive silicone composition, automotive part, electrical and electronic part, and heat dissipation material

JP2025035685AActive Publication Date: 2025-03-14SHIN ETSU CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023142901
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14
Estimated Expiration
2043-09-04

AI Technical Summary

Benefits of technology

【0009】 本発明の縮合硬化型熱伝導性シリコーン組成物は、特に、可使時間が長く、室温にて湿気で硬化し、更に軟らかく、耐熱性に優れ、熱伝導性も高い硬化物(シリコーンゴム)を与えることから、電気電子·車載用放熱材料として好適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035685000001
    Figure 2025035685000001
  • Figure 2025035685000002
    Figure 2025035685000002
  • Figure 2025035685000003
    Figure 2025035685000003
Patent Text Reader

Abstract

To provide a condensation-curable thermally conductive silicone composition that has a long pot life, cures by moisture at room temperature, and forms a soft cured product suitable for stress relaxation applications, the cured product also exhibiting excellent heat resistance, as well as an automotive part, an electrical and electronic part, and a heat dissipation material.SOLUTION: A condensation-curable thermally conductive silicone composition employs a specific amount of an organic catalyst having a guanidine group adjacent to a urea bond in the molecule. The condensation-curable thermally conductive silicone composition is capable of delaying curing, extending pot life, and forming a soft cured product with excellent heat resistance.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a condensation-curable thermally conductive silicone composition that has a long pot life and can be cured with moisture at room temperature to form a soft cured product (rubber), as well as to automotive parts, electrical and electronic parts, and heat dissipating materials. [Background technology]

[0002] In the fields of electrical and electronic equipment and transportation machinery, more electronic control elements and components are being installed than ever before in order to precisely manage energy. For example, even when focusing only on transportation machinery, the change from gasoline-powered vehicles to hybrid vehicles, plug-in hybrid vehicles, electric vehicles, etc. has made it necessary to install electronic elements and components such as motors, inverters, and batteries that were not necessary in gasoline-powered vehicles until now. Thermally conductive silicone compositions are now becoming indispensable in order to efficiently transfer heat from these heat-generating electronic elements and components to coolers.

[0003] Furthermore, in recent years, since it is necessary to mount a large number of electronic elements and components in a limited space, the mounting environment (temperature, angle, etc.) has become more diverse. For example, the heat-generating electronic elements and components and the cooling plate are no longer placed horizontally, and the thermally conductive material connecting them is often mounted at a certain inclination. In such a usage environment, in order to prevent the thermally conductive material from dripping out from between the heat generating body and the cooling body, a thermally conductive silicone adhesive material or a thermally conductive potting material or a room temperature curing type thermally conductive silicone rubber composition may be used (JP Patent Publication No. 8-208993, JP Patent Publication No. 61-157569, JP Patent Publication No. 2004-352947, Japanese Patent No. 3543663, and Japanese Patent No. 4255287: Patent Documents 1 to 5). However, in all cases, the adhesion is complete, so there is a drawback in that reworkability is poor. In addition, because the thermally conductive material becomes very hard after bonding, it cannot withstand repeated stress caused by thermal distortion and may peel off from the heat-generating element, causing a sudden rise in thermal resistance, or may place stress on electronic elements and components after hardening.

[0004] In order to solve the above problems, a condensation-curing type heat dissipation material has been proposed (Patent Publication No. 5846323: Patent Document 6). By using this technology, it is possible to obtain a thermally conductive material that can ensure a certain degree of reworkability even after curing, does not drip after curing, and remains soft and grease-like after curing, so can also function as a stress reliever, and is less susceptible to curing inhibition by contaminants. However, conventional condensation-curing type thermally conductive silicone compositions have the disadvantage that their applications are limited due to their fast curing and short pot life. In addition to the above-mentioned documents, the following documents can be mentioned as prior art related to the present invention. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 8-208993 [Patent Document 2] Japanese Unexamined Patent Publication No. 61-157569 [Patent Document 3] JP 2004-352947 A [Patent Document 4] Patent No. 3543663 [Patent Document 5] Patent No. 4255287 [Patent Document 6] Patent No. 5846323 [Patent Document 7] JP 2013-001670 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and has as its object to provide a condensation-curable thermally conductive silicone composition which has a long pot life, cures with moisture at room temperature, and gives a cured product which is soft and therefore suitable for stress relaxation applications, and which also gives a cured product which has excellent heat resistance, as well as to provide automotive parts, electrical and electronic parts, and heat dissipating materials. [Means for solving the problem]

[0007] The present inventors conducted extensive research to achieve the above object, and discovered that a condensation-curable heat-conductive silicone composition using a specific amount of an organic catalyst having a guanidine group adjacent to a urea bond in the molecule can delay curing and extend the usable time. In addition, the cured product of the composition is soft and has good heat resistance, so it is suitable for use in automobile parts, electrical and electronic parts, heat dissipation materials, etc., and this led to the invention.

[0008] Accordingly, the present invention provides the following condensation-curable thermally conductive silicone composition, as well as automotive parts, electric and electronic parts, and heat dissipating materials. 1. (A) an organopolysiloxane having a viscosity of 50 to 50,000 mPa s at 23°C, represented by the following general formula (1): 10 to 70 parts by mass, HO-(SiR 12O) m -H (1) (In the formula, R 1 is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and each R 1 may be the same or different groups. m is an integer of 20 or more. (B) an organopolysiloxane represented by the following general formula (2): 30 to 90 parts by mass, (However, the total amount of components (A) and (B) is 100 parts by mass.) [ka] (In the formula, R 2 are independently unsubstituted or substituted monovalent hydrocarbon radicals; R 3 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, n is an integer of 2 to 100, and a is an integer of 1 to 3. (C) at least one selected from the group consisting of a silane compound having three or more hydrolyzable groups bonded to silicon atoms in one molecule, which is represented by the following general formula (3), and a partial hydrolyzate and a partial hydrolyzed condensate thereof other than the component (B): 1 to 30 parts by mass, R 4 b Six 4-b (3) (In the formula, R 4 is an unsubstituted or halogen-substituted monovalent hydrocarbon group, and X is independently a hydrolyzable group. b is 0 or 1. (D) a curing catalyst represented by the following general formula (4): 0.01 to 10 parts by mass, [ka] (In the formula, R 5 are each independently a hydrogen atom, a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 6 carbon atoms; R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group; R 7 are independently an unsubstituted or substituted monovalent hydrocarbon group, c is an integer from 1 to 3, and d is an integer from 1 to 10. (E) Thermally conductive filler with a thermal conductivity of 10 W / (m K) or more: 100 to 2,000 parts by mass a condensation-curable thermally conductive silicone composition having, as an essential component, a Shore OO hardness of 10 to 90 at 23°C after being left for 7 days in an environment of 23±2°C and 50±5% RH. 2. The condensation-curable thermally conductive silicone composition according to [1], which has a tack-free time of 10 minutes or longer. 3. A condensation-curable thermally conductive silicone composition as described in [1] or [2], which has a thermal conductivity of at least 0.5 W / (m·K) after curing. 4. The condensation-curable thermally conductive silicone composition according to any one of [1] to [3], further comprising (F) 0.01 to 30 parts by mass of a silane compound and / or a partial hydrolysis condensate thereof, the silane compound having a functional group selected from the group consisting of an amino group, an epoxy group, a mercapto group, an acryloyl group, and a methacryloyl group, bonded to a silicon atom via a carbon atom, and having a hydrolyzable group bonded to a silicon atom, per 100 parts by mass of the combined total of the components (A) and (B). 5. An automobile part having a cured product of the condensation-curable heat-conductive silicone composition according to any one of [1] to [4]. 6. An electric or electronic part having a cured product of the condensation-curable thermally conductive silicone composition according to any one of [1] to [4]. 7. A heat dissipating material comprising a cured product of the condensation-curable thermally conductive silicone composition according to any one of [1] to [4]. Effect of the Invention

[0009] The condensation-curable thermally conductive silicone composition of the present invention has a particularly long pot life, cures with moisture at room temperature, and gives a cured product (silicone rubber) that is soft, has excellent heat resistance, and has high thermal conductivity, making it ideal as a heat-dissipating material for electrical, electronic, and automotive applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The condensation-curable thermally conductive silicone composition of the present invention contains the following components (A) to (E): Here, room temperature refers to 23°C±15°C, and preferably 20 to 25°C.

[0011] [Component (A): Organopolysiloxane] The organopolysiloxane of the component (A) is represented by the following general formula (1). HO-(SiR 1 2O) m -H (1) (In the formula, R 1 is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and each R 1 may be the same or different groups. m is an integer of 20 or more.

[0012] As shown in general formula (1) above, component (A) is a linear diorganopolysiloxane whose main chain is composed of repeating diorganosiloxane units and whose molecular chain is terminally blocked with hydroxyl groups (silanol groups) bonded to silicon atoms and has a viscosity of 50 to 50,000 mPa s at 23°C, and which acts as the main agent (base polymer) for the condensation-curable thermally conductive silicone composition of the present invention.

[0013] In the general formula (1), R 1 is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms, and examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, hexyl, octyl, and 2-ethylhexyl groups; cycloalkyl groups such as cyclohexyl groups; alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, and hexenyl groups; aryl groups such as phenyl and tolyl groups; and aralkyl groups such as benzyl and phenylethyl groups. Alternatively, examples of R include groups in which the hydrogen atoms of these hydrocarbon groups are partially substituted with halogen atoms such as fluorine, chlorine, and bromine, such as a trifluoropropyl group. 1The unsubstituted or substituted monovalent hydrocarbon group of R is preferably one that does not contain an aliphatic unsaturated bond, specifically, an alkyl group such as a methyl group, or an aryl group such as a phenyl group, and a methyl group is particularly preferred. 1 may be the same group or different groups.

[0014] In the general formula (1), the difunctional diorganosiloxane unit ((SiR 1 2O 2 / 2 m, which indicates the number of repetitions (or degree of polymerization) of the formula (1), is an integer of 20 or more, preferably an integer of 50 to 1,000, more preferably an integer of 100 to 800, and particularly preferably an integer of 200 to 700. If m is less than 20, the resulting cured product will be hard and the stress relaxation performance will be reduced, and if m exceeds 1,000, the viscosity of the composition will be high, which may reduce workability.

[0015] The viscosity of the organopolysiloxane of component (A) at 23°C is in the range of 50 to 50,000 mPa·s, preferably in the range of 300 to 30,000 mPa·s, and more preferably in the range of 500 to 20,000 mPa·s. If the viscosity at 23°C is less than 50 mPa·s, the resulting cured product will be hard and the stress relaxation performance will be reduced, while if it exceeds 50,000 mPa·s, the viscosity of the composition will be high and workability will be reduced. In the present invention, the viscosity can be measured using a rotational viscometer (for example, BL type, BH type, BS type, cone-plate type, etc.).

[0016] In the present invention, the degree of polymerization (or molecular weight) can be determined, for example, as a polystyrene-equivalent number-average degree of polymerization (or number-average molecular weight) in gel permeation chromatography (GPC) analysis using toluene, tetrahydrofuran (THF) or the like as a developing solvent. The organopolysiloxane of the component (A) may be used alone or in combination of two or more different types.

[0017] The amount of component (A) used is in the range of 10 to 70 parts by mass, preferably 20 to 60 parts by mass, and more preferably 30 to 50 parts by mass, since less than 10 parts by mass of the combined total of components (A) and (B) will result in the composition not curing, and more than 70 parts by mass will result in the cured product being too hard.

[0018] [Component (B): Organopolysiloxane having a hydrolyzable group at one end] Component (B) is an organopolysiloxane represented by the following general formula (2): Component (B) plays the important role of imparting an appropriate hardness (softness) to the resulting cured product. [ka] (In the formula, R 2 are independently unsubstituted or substituted monovalent hydrocarbon radicals; R 3 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, n is an integer of 2 to 100, and a is an integer of 1 to 3.

[0019] In the general formula (2), R 2are independently unsubstituted or substituted monovalent hydrocarbon groups having preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 3 carbon atoms, examples of which include linear alkyl groups, branched alkyl groups, cyclic alkyl groups, alkenyl groups, aryl groups, aralkyl groups, halogenated alkyl groups, and cyanoalkyl groups. Examples of linear alkyl groups include methyl groups, ethyl groups, propyl groups, hexyl groups, and octyl groups. Examples of branched alkyl groups include isopropyl groups, isobutyl groups, tert-butyl groups, and 2-ethylhexyl groups. Examples of cyclic alkyl groups include cyclopentyl groups and cyclohexyl groups. Examples of alkenyl groups include vinyl groups and allyl groups. Examples of aryl groups include phenyl groups and tolyl groups. Examples of aralkyl groups include 2-phenylethyl groups and 2-methyl-2-phenylethyl groups. Examples of halogenated alkyl groups include 3,3,3-trifluoropropyl, 2-(nonafluorobutyl)ethyl, and 2-(heptadecafluorooctyl)ethyl groups. Examples of cyanoalkyl groups include cyanoethyl groups. R 2 is preferably a methyl group, a phenyl group, or a vinyl group.

[0020] In the general formula (2), R 3 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group. Examples of the alkyl group include the above R 2 Examples of the alkoxyalkyl group include those having 2 to 10 carbon atoms, such as a methoxyethyl group and a methoxypropyl group. Examples of the alkenyl group include those having 2 to 10 carbon atoms, such as the above-mentioned R 2 Examples of the acyl group include those having 2 to 10 carbon atoms, such as an acetyl group and an octanoyl group. R 3 As the alkyl group, an alkyl group is preferable, and a methyl group or an ethyl group is particularly preferable.

[0021] In general formula (2), n is an integer of 2 to 100, and preferably an integer of 5 to 80. If n is less than 2, the resulting cured product of the condensation-curable heat-conductive silicone composition is prone to oil bleeding and dripping. If n is more than 100, the viscosity of the resulting condensation-curable heat-conductive silicone composition is too high, which reduces the ease of application. a is an integer of 1 to 3, and is preferably 3.

[0022] The viscosity of component (B) at 23° C. is usually from 5 to 10,000 mPa·s, and preferably from 5 to 5,000 mPa·s.

[0023] Specific examples of suitable components (B) include the following: [ka] (In the formula, Me is a methyl group.) The component (B) may be used alone or in combination of two or more types.

[0024] If the amount of this (B) component is less than 30 parts by mass, based on 100 parts by mass of the combined total of the (A) and (B) components, the product will become hard after curing and a soft cured product will not be obtained. If the amount is more than 90 parts by mass, the product will not cure. Therefore, the (B) component is used in the range of 30 to 90 parts by mass, preferably 40 to 80 parts by mass, and more preferably 50 to 70 parts by mass.

[0025] [Component (C): Hydrolyzable organosilane compounds, their partial hydrolyzates, and their partial hydrolyzed condensates] Component (C) is a silane compound other than component (B) having three or more hydrolyzable groups bonded to silicon atoms in one molecule, or a partial hydrolyzate or partial hydrolyzed condensate thereof (i.e., a siloxane oligomer having three or more residual hydrolyzable groups in one molecule), and acts as a crosslinking agent for the composition of the present invention. The silane compound is represented by the following general formula (3). R 4b Six 4-b (3) (In the formula, R 4 is an unsubstituted or halogen-substituted monovalent hydrocarbon group, and X is independently a hydrolyzable group. b is 0 or 1, preferably 1.

[0026] In the general formula (3), examples of X, which is a hydrolyzable group, include ketoxime groups, alkoxy groups, acyloxy groups, and alkenyloxy groups.Specific examples include ketoxime groups having 3 to 8 carbon atoms, such as dimethylketoxime groups, methylethylketoxime groups, and methylisobutylketoxime groups; alkoxy groups having 1 to 4, particularly 1 or 2, carbon atoms, such as methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, isobutoxy groups, sec-butoxy groups, and tert-butoxy groups; acyloxy groups having 2 to 4 carbon atoms, such as acetoxy groups and propionoxy groups; and alkenyloxy groups having 2 to 5 carbon atoms, such as vinyloxy groups, allyloxy groups, propenoxy groups, isopropenoxy groups, and (cyclopent-1-en-1-yl)oxy groups.X may be the same group or different groups.

[0027] In addition, in the general formula (3), the remaining group R bonded to the silicon atom other than the hydrolyzable group 4 is not particularly limited as long as it is an unsubstituted or halogen-substituted monovalent hydrocarbon group, specific examples include unsubstituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms, such as alkyl groups such as methyl, ethyl, propyl, and butyl, alkenyl groups such as vinyl, and aryl groups such as phenyl, as well as halogen-substituted monovalent hydrocarbon groups such as chloromethyl and trifluoropropyl, in which some of the hydrogen atoms bonded to the carbon atoms of the unsubstituted monovalent hydrocarbon group are substituted with halogen atoms such as fluorine, chlorine, and bromine. Among these, unsubstituted monovalent hydrocarbon groups are preferred, and methyl, ethyl, vinyl, and phenyl groups are more preferred.

[0028] Specific examples of such component (C) include ketoxime silanes such as tetrakis(methylethylketoxime)silane, methyltris(dimethylketoxime)silane, methyltris(methylethylketoxime)silane, ethyltris(methylethylketoxime)silane, methyltris(methylisobutylketoxime)silane, and vinyltris(methylethylketoxime)silane; alkoxysilanes such as methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, tetramethoxysilane, and tetraethoxysilane; and methyltriacetoxysilane.

[0113] Examples of the silanes include acyloxysilanes such as acetoxysilanes, such as vinyltriacetoxysilane and phenyltriacetoxysilane; isopropenoxysilanes, such as methyltriisopropenoxysilane, vinyltriisopropenoxysilane and phenyltriisopropenoxysilane; alkenyloxysilanes such as silyl enol ethers, such as methyltris[(cyclopent-1-en-1-yl)oxy]silane, vinyltris[(cyclopent-1-en-1-yl)oxy]silane and phenyltris[(cyclopent-1-en-1-yl)oxy]silane; and partial hydrolysates and partial hydrolyzed condensates of these silanes, with alkenyloxysilanes being more preferred. These may be used alone or in combination of two or more.

[0029] The amount of this component (C) to be used is 1 to 30 parts by mass, preferably 2 to 28 parts by mass, and more preferably 5 to 25 parts by mass, because if it is less than 1 part by mass, the composition will not harden, and if it is more than 30 parts by mass, the time until hardening will be longer, relative to 100 parts by mass of the combined total of the components (A) and (B).

[0030] [Component (D): An organic catalyst having a guanidine group adjacent to a urea bond in the molecule] Component (D) is an organic catalyst (curing catalyst) having a guanidine group adjacent to a urea bond in the molecule, and is a compound having a structure represented by the following general formula (4). Use of this catalyst can impart an appropriate pot life to the composition of the present invention. [ka] (In the formula, R 5 are each independently a hydrogen atom, a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 6 carbon atoms; R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group; R 7 are independently an unsubstituted or substituted monovalent hydrocarbon group, c is an integer from 1 to 3, and d is an integer from 1 to 10.

[0031] In the general formula (4), R 5 each independently represents a hydrogen atom, a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 6 carbon atoms. Examples of the alkyl group include a hydrogen atom, a methyl group, an ethyl group, a propyl group, a butyl group, an isobutyl group, a tert-butyl group, a vinyl group, a propenyl group, and a cyclohexyl group, and preferably a hydrogen atom, a methyl group, an ethyl group, or a cyclohexyl group.

[0032] In the general formula (4), R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group. Examples of the alkyl group include the above R 2 Examples of the alkoxyalkyl group include those having 2 to 10 carbon atoms, such as a methoxyethyl group and a methoxypropyl group. Examples of the alkenyl group include those having 2 to 10 carbon atoms, such as the above-mentioned R 2 Examples of the acyl group include those having 2 to 10 carbon atoms, such as an acetyl group and an octanoyl group. R 6 As the alkyl group, an alkyl group is preferable, and a methyl group or an ethyl group is particularly preferable.

[0033] In the general formula (4), R 7 are independently unsubstituted or substituted monovalent hydrocarbon groups, and R 2 Examples of the groups include the same groups as those exemplified in 1. An alkyl group is preferable, and a methyl group or an ethyl group is particularly preferable.

[0034] In formula (4), c is an integer of 1 to 3, and preferably 2 or 3. d is an integer of 1 to 10, preferably 2 to 8, and particularly preferably 3 to 5.

[0035] Specific examples of suitable components (D) include the following: [ka] (In the formula, Me is a methyl group, and Et is an ethyl group.) The component (D) may be used alone or in combination of two or more types.

[0036] The method for producing the component (D) is publicly known. For example, as described in JP 2013-001670 A, the component can be produced by reacting an alkoxysilane having an isocyanate group with a guanidine compound.

[0037] The amount of component (D) added is in the range of 0.01 to 10 parts by mass, and preferably in the range of 0.1 to 5 parts by mass, per 100 parts by mass of the total of components (A) and (B). If the amount of component (D) added is too small, the composition will not cure, whereas if the amount is too large, the composition will cure too quickly, shortening the pot life.

[0038] [Component (E): Thermally conductive filler] If the thermal conductivity of the thermally conductive filler of component (E) is less than 10 W / (m·K), the thermal conductivity of the condensation-curable thermally conductive silicone composition itself will be low, so a filler with a thermal conductivity of 10 W / (m·K) or more, preferably 15 W / (m·K) or more, is used. Examples of such thermally conductive fillers include aluminum powder, copper powder, silver powder, nickel powder, gold powder, alumina powder, zinc oxide powder, magnesium oxide powder, aluminum nitride powder, boron nitride powder, silicon nitride powder, diamond powder, and carbon powder, but any filler with a thermal conductivity of 10 W / (m·K) or more may be used, and one type or a mixture of two or more types may be used.

[0039] The average particle size of the thermally conductive filler is preferably in the range of 0.1 to 200 μm, more preferably in the range of 0.1 to 150 μm, since if it is smaller than 0.1 μm, the viscosity may be high and the composition may be poor in workability, and if it is larger than 200 μm, the uniformity of the condensation curing type thermally conductive silicone composition may be poor. The shape of the filler may be any shape, such as amorphous or spherical. The average particle size can be determined, for example, as the weight average value (or median diameter) by the laser light diffraction method.

[0040] The amount of component (E) blended is in the range of 100 to 2,000 parts by mass, and preferably 500 to 1,800 parts by mass, based on 100 parts by mass of the combined total of components (A) and (B). If the amount is less than 100 parts by mass, the desired thermal conductivity cannot be obtained, and if the amount is more than 2,000 parts by mass, the composition becomes difficult to work with.

[0041] [Component (F): Silane coupling agent and / or partial hydrolysis condensate thereof] The condensation-curable heat-conductive silicone composition of the present invention may further contain, as component (F), a silane compound and / or a partial hydrolysis condensate thereof, which has a functional group selected from the group consisting of amino groups, epoxy groups, mercapto groups, acryloyl groups, and methacryloyl groups bonded to a silicon atom via a carbon atom and also has a hydrolyzable group bonded to a silicon atom. This component plays a role in increasing the adhesion between the composition of the present invention and the surface (substrate) to which it is applied.

[0042] The silane compound and its partial hydrolysis condensate preferably have 1 to 3, more preferably 2 or 3 hydrolyzable groups. When the silane compound and its partial hydrolysis condensate have two or more of the above functional groups, they may be bonded to the silicon atom via different carbon atoms, or may be bonded to the silicon atom via the same carbon atom. Examples of the hydrolyzable group include the same as the hydrolyzable group X in the general formula (3) of the component (C), and among them, an alkoxy group is preferred.

[0043] Specific examples of the silane compound include amino group-containing silanes such as 3-aminopropyldimethoxymethylsilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyldimethoxymethylsilane, 3-(2-aminoethylamino)propyltrimethoxysilane, 2-aminoethylaminomethyldimethoxymethylsilane, and 2-aminoethylaminomethyltrimethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, 3-glycidoxyethyltrimethoxysilane, and 3-glycidoxyethyl Examples of the silanes include epoxy group-containing silanes such as dimethoxymethylsilane, mercapto group-containing silanes such as γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and γ-mercaptopropylmethyldiethoxysilane, and (meth)acryloyl group (acryloyl group or methacryloyl group)-containing silanes such as methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, methacryloxypropylmethyldimethoxysilane, acryloxypropyltrimethoxysilane, and acryloxypropyltriethoxysilane. The component (F) is not limited to one of these, and may be used as a mixture of two or more of them.

[0044] When the above-mentioned (F) component is blended, the blending amount of less than 0.01 part by mass relative to 100 parts by mass of the combined total of the (A) and (B) components is preferably in the range of 0.01 to 30 parts by mass, and more preferably in the range of 0.1 to 20 parts by mass, since the effect is weak and adhesiveness may not be exhibited if the blending amount is less than 0.01 part by mass, whereas if the blending amount is more than 30 parts by mass, no improvement in adhesiveness is observed and it is uneconomical.

[0045] In addition, in the condensation curing type heat conductive silicone composition of the present invention, generally known additives other than the above-mentioned components (A) to (F) may be used within the scope of the present invention without impairing the purpose of the present invention. Examples of additives include polyethers as thixotropy improvers, silicone oils as plasticizers, isoparaffins, etc., and as necessary, colorants such as pigments, dyes, and fluorescent whitening agents, and biologically active additives such as fungicides, antibacterial agents, and marine organism repellents can be added. In addition, surface modifiers such as phenyl silicone oil, alkyl modified silicone oil, and fluorosilicone oil for improving reworkability, silicone resins for improving strength, and organic liquids incompatible with silicone, as well as solvents such as toluene, xylene, solvent volatile oils, cyclohexane, methylcyclohexane, and low boiling point isoparaffins can also be added.

[0046] The condensation-curable, heat-conductive silicone composition of the present invention can be prepared by uniformly mixing the above-mentioned components by a known method. The viscosity of the resulting condensation-curable, heat-conductive silicone composition at 23°C is preferably 10 to 300 Pa s, and more preferably 30 to 250 Pa s.

[0047] The condensation curable heat conductive silicone composition of the present invention has a Shore OO hardness of 10 to 90, preferably 30 to 70, at 23°C after being left for 7 days (after curing) in an environment of 23±2°C and 50±5% RH. If the hardness is less than 10, the composition after curing is too soft, causing pump-out due to deterioration over time and making it impossible to obtain suitable heat dissipation performance, whereas if the hardness is more than 90, the stress relaxation performance is poor and defects occur in electronic elements or heat dissipation materials due to thermal distortion. The hardness can be measured according to the method specified in ISO 7619-1. Furthermore, in the condensation-curable thermally conductive silicone composition of the present invention, the above hardness range can be achieved by mixing the organopolysiloxane of component (A) and the organopolysiloxane having a hydrolyzable group at one end of component (B) in amounts of 10 to 70 parts by mass of component (A) and 30 to 90 parts by mass of component (B) for a total of 100 parts by mass, and adding a filler to form a composition.

[0048] The condensation-curable heat-conductive silicone composition of the present invention preferably has a tack-free time of 10 minutes or more, and more preferably 20 minutes or more, at 23° C. The tack-free time can be measured according to the method specified in JIS A 5758. The condensation-curable heat-conductive silicone composition of the present invention can achieve the above tack-free time by adding an organic catalyst having a guanidine group adjacent to a urea bond in the molecule of component (D) to the composition in an amount of 0.01 to 10 parts by mass per 100 parts by mass of the total of components (A) and (B).

[0049] Furthermore, the condensation-curable thermally conductive silicone composition of the present invention preferably has a thermal conductivity of 0.5 W / (m·K) or more, and more preferably 2 W / (m·K) or more at 23°C after curing. Thermal conductivity can be measured by the hot disk method in accordance with ISO 22007-2. In addition, the condensation-curable thermally conductive silicone composition of the present invention can achieve the above thermal conductivity by adding component (E) having a thermal conductivity of 10 W / (m·K) or more to the composition in an amount of 100 to 2,000 parts by mass per 100 parts by mass of the total of components (A) and (B).

[0050] As described above, the condensation curable heat conductive silicone composition obtained in this manner has a long pot life and the obtained cured product maintains its softness, so when used as a heat dissipation material such as a gap filler, it has excellent reworkability and there is no need to worry about applying a large amount of stress to electronic elements. Furthermore, since it has good heat resistance, it can be used in a wide range of fields that require heat dissipation and heat resistance, such as the electrical and electronic fields and the transportation fields. In particular, it is suitable for use in automotive parts, electrical and electronic parts, and heat dissipation materials. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In order to clarify the advantages of the present invention, specific examples are shown to prove the invention. In the following formula, Me is a methyl group, and Et is an ethyl group. The viscosity of the following component (A) is a value measured using a rotational viscometer (BII type viscometer BHII, manufactured by Toki Sangyo Co., Ltd.) at 23°C in accordance with the method specified in JIS Z 8803, and the average particle size of the following component (E) is a value measured using a laser diffraction type particle measuring device (product name Mastersizer 3000, manufactured by Malvern Panalytical).

[0052] First, the following components were prepared. Component (A) A-1: Dimethylpolysiloxane with a viscosity of 5,000 mPa s at 23°C and both ends capped with hydroxyl groups (m in formula (1) = 390) A-2: Dimethylpolysiloxane with a viscosity of 20,000 mPa s at 23°C and both ends blocked with hydroxyl groups (m in formula (1) = 610)

[0053] (B) Component Organopolysiloxane represented by the following formula: B-1: [ka] B-2: [ka]

[0054] (C) Component C-1: Phenyltriisopropenoxysilane C-2: Vinyltris[(cyclopent-1-en-1-yl)oxy]silane

[0055] (D) Component An organic catalyst having a guanidine group adjacent to a urea bond in the molecule represented by the following formula: D-1: [ka] D-2: [ka] D-3 (for comparison): Tetramethylguanidylpropyltrimethoxysilane D-4 (for comparison): Tetramethylguanidine

[0056] (E) Component E-1: Alumina powder with an average particle size of 10 μm (thermal conductivity: 27 W / (m K)) E-2: Aluminum nitride powder with an average particle size of 20 μm (thermal conductivity: 170 W / (m·K))

[0057] Ingredient (F) The following amino group-containing silanes F-1: 3-aminopropyltriethoxysilane

[0058] [Examples 1 to 5 and Comparative Examples 1 to 3] The components (A) to (F) were mixed in the amounts shown in Table 1 as follows to obtain condensation curable heat conductive silicone compositions of Examples and Comparative Examples. The components (A), (B) and (E) were charged into a mixer (5XDMV-R, Dalton Co., Ltd.) in the amounts shown in Table 1, and were degassed and heated and mixed at 150°C for 3 hours. The mixture was then cooled to room temperature, and the components (C) and (D) were added, and the mixture was degassed and mixed at room temperature to become uniform. If necessary, the component (F) was added, and the mixture was degassed and mixed at room temperature to become uniform. The condensation curable heat conductive silicone compositions thus obtained were evaluated for tack-free time, viscosity, hardness and thermal conductivity by the methods described below. Each evaluation was performed at 23°C. The results are shown in Table 1.

[0059] [Dry time to touch] The tack-free time was measured according to the method specified in JIS A 5758.

[0060] [Viscosity Evaluation] The viscosity is shown as a value at 23° C., and was measured using a capillary rheometer (manufactured by Malvern Instruments, Inc., RH2000).

[0061] [Initial hardness evaluation] The condensation-curable thermally conductive silicone composition was cut into a 2.0 mm sheet and left to cure for 7 days at 23±2°C / 50±5% RH, after which the Shore OO hardness was measured in accordance with the method specified in ISO 7619-1.

[0062] [Hardness evaluation after heat resistance] The condensation-curable thermally conductive silicone composition was cut into a 2.0 mm sheet and left to cure for 7 days at 23±2°C / 50±5% RH. After this, a heat resistance test was carried out at 150°C for 250 hours, and then the temperature was returned to 23°C, after which the Shore OO hardness was measured in accordance with the method specified in ISO 7619-1.

[0063] [Thermal conductivity evaluation] The condensation curable thermally conductive silicone composition was cut into a 6.0 mm sheet and left to cure for 7 days at 23±2°C / 50±5% RH, after which the thermal conductivity was measured using a Kyoto Electronics Manufacturing Co., Ltd. hot disc method thermal property measurement device TPA-501.

[0064] [Table 1]

[0065] The above results show that the condensation-curable thermally conductive silicone compositions of the Examples have a tack-free time of 10 minutes or more, a long pot life, maintain soft physical properties at Shore OO hardness levels after curing and after heat resistance tests, and also have high thermal conductivity. On the other hand, the condensation-curable thermally conductive silicone composition of the Comparative Example has a tack-free time of only a few minutes and a short pot life. This demonstrates that the condensation-curable thermally conductive silicone composition of the present invention is able to extend the pot life.

Claims

1. (A) an organopolysiloxane having a viscosity of 50 to 50,000 mPa·s at 23° C., represented by the following general formula (1): 10 to 70 parts by mass, HO-(SiR 1 2 O) m -+ (1) (In the formula, R 1 is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and each R 1 may be the same or different groups. m is an integer of 20 or more. (B) an organopolysiloxane represented by the following general formula (2): 30 to 90 parts by mass, (However, the total amount of components (A) and (B) is 100 parts by mass.) 【Chemistry 1】 (In the formula, R 2 are independently unsubstituted or substituted monovalent hydrocarbon groups; R 3 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, n is an integer from 2 to 100, and a is an integer from 1 to 3. (C) 1 to 30 parts by mass of at least one selected from the group consisting of a silane compound other than component (B) having three or more hydrolyzable groups bonded to silicon atoms in one molecule, which is represented by the following general formula (3), a partial hydrolyzate thereof, and a partial hydrolyzed condensate thereof: R 4 b SiX 4-b (3) (In the formula, R 4 is an unsubstituted or halogen-substituted monovalent hydrocarbon group, and X is independently a hydrolyzable group; b is 0 or 1. (D) a curing catalyst represented by the following general formula (4): 0.01 to 10 parts by mass, 【Chemistry 2】 (In the formula, R 5 are each independently a hydrogen atom, a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, or an alkenyl group having 2 to 6 carbon atoms; R 6 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group; R 7 are independently an unsubstituted or substituted monovalent hydrocarbon group, c is an integer from 1 to 3, and d is an integer from 1 to 10. (E) Thermally conductive filler having a thermal conductivity of 10 W / (m K) or more: 100 to 2,000 parts by mass a condensation-curable thermally conductive silicone composition having an essential component of the above, and having a Shore OO hardness of 10 to 90 at 23°C after being left for 7 days in an environment of 23±2°C and 50±5% RH.

2. 2. The condensation-curable thermally conductive silicone composition according to claim 1, which has a tack-free time of 10 minutes or greater.

3. 2. The condensation-curable thermally conductive silicone composition according to claim 1, which has a thermal conductivity after curing of at least 0.5 W / (m·K).

4. The condensation-curable thermally conductive silicone composition according to claim 1, further comprising 0.01 to 30 parts by mass of (F) a silane compound and / or a partial hydrolysis condensate thereof, the silane compound having a functional group selected from the group consisting of an amino group, an epoxy group, a mercapto group, an acryloyl group, and a methacryloyl group, bonded to a silicon atom via a carbon atom, and having a hydrolyzable group bonded to a silicon atom, per 100 parts by mass of the total of the components (A) and (B).

5. 5. An automobile part comprising a cured product of the condensation-curable heat-conductive silicone composition according to any one of claims 1 to 4.

6. 5. An electric or electronic part comprising a cured product of the condensation-curable thermally conductive silicone composition according to any one of claims 1 to 4.

7. A heat dissipating material comprising a cured product of the condensation-curable thermally conductive silicone composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Organosilicon compound and room temperature vulcanizing organopolysiloxane composition

    JP2013001670A

  • Electronic device excellent in heat dissipation and reworkability and manufacturing method thereof

    JP2013222836A

  • Smectic liquid crystal display

    JP1983046323A

  • Thermally conductive adhesive composition

    JP1986157569A

  • Heat-conductive silicone composition

    JP1996208993A